Research in African language and linguistics (2014)
Classical authors such as Livy, Marcus Aurelius, Dio Cassius have all, in their treatises on the ancient Roman society mentioned occurrences of plagues and their devastating effects on both humans and animals. In analyzing the plagues, some Modern commentaries on the Greaco-Roman world have postulated different theories and have drawn conclusions as to what these plagues actually were for ancient authors merely mentioned the diseases as plagues or epidemics. Modem authors on Ibadan have also mentioned the regular occurrences of the cholera epidemics in the city. The aim of this paper is to examine the plagues or epidemics that occurred in the Greaco-Roman world and the cholera epidemics in Ibadan. It attempts to examine factors responsible for the plagues and epidemics in both societies and the methods adopted in combating the epidemics. This paper concludes with the thrust that because the ancients were not fully conversant with these plagues, high mortality was recorded. For modern Ibadan, lack of safe water, proper sanitation and food safety among others, caused the preponderance and repeated occurrences of the cholera epidemics and its effects in Ibadan. Further studies can interrogate alternative medicine towards health care in the events of plagues and epidemics in both ancient Rome and modem Ibadan